Penggunaan Media Sosial Youtube dalam Pembelajaran Sejarah Kebudayaan Islam di Madrasah Ibtidaiyah - Atiqoh, Laili Ida; Mas'uliyyah, Mas'uliyyah; Munawir, Munawir (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
The use of YouTube social media in learning the history of Islamic culture at Madrasah Ibtidaiyah aims to find out how effective the use of YouTube media is in learning carried out for students at the Madrasah Ibtidaiyah level. This research is a type of qualitative research, in this qualitative research data is collected, which means the data sources needed and also the data collection tools can change according to a need. It can also use existing research in journals so that it can analyze it using existing journal findings so that there is data that can be used. The results of the study stated that the use of YouTube social media can create effectiveness in learning Islamic Cultural History and in other subjects because it can be seen how many benefits there are from YouTube social media for learning Islamic Cultural History. However, when students use teacher social media while learning at school or at home, teachers and parents must continue to monitor how students use YouTube in learning, so students don't use it carelessly. Keywords: Social media, YouTube, Learning The History Of Islamic Culture